STUDY OF COAL SELF-HEATING ASAM-ASAM SITE PT ARUTMIN INDONESIA BY USING ADIABATIC HEATING METHOD AT LABORATORY SCALE - Gusnaidi Ginting, Edwin
Spontaneous combustion is a process of slow heating and oxidation of coal that can occur spontaneously without an external heat source. This phenomenon usually occurs when coal is stored in storage/stockpile for a long period, in the process of coal transportation, and in PLTU storage. This research focuses on studying the self-ignition potential of coal at PT Arutmin Indonesia's Asam-Asam site and examining the intrinsic influence of coal on self-ignition potential. The coal particle size used in this study is -60 +80 mesh. In this study, the adiabatic heating method initiated by Beamish (2000) concerning SNI 9239: 2023 was used, namely coal was preheated for 16 hours using Nitrogen with a discharge of 0.1 L/min at a temperature of 110 ºC, then continued with coal combustion using Oxygen with a discharge of 0.05 L/min with an initial combustion temperature of 40 ºC. The test results show that the Asam-Asam site coal is classified as Subbituminous B Coal with an R70 value of 8.82 °C/h, which is included in class VI (ultra high) based on the Queensland R70 index and class V (very high) based on the New South Wales R70 index. The self-combustion potential of coal is influenced by intrinsic characteristics such as moisture, ash, volatile matter, and fixed carbon content. Increasing moisture content to 25% increases the R70 value, while higher ash content tends to decrease the R70 value. High volatile matter levels also affect the self-combustion process, while fixed carbon has a weak correlation with R70 values.